Togo : Technical Assistance Report-National Accounts Statistics. (IMF Staff Country Reports; Country Report ;, 2020)
A technical assistance (TA) mission led by Mr. Fahd Ndiaye, Resident Adviser in Real Sector Statistics for AFRITAC West, visited Lome from January 27 to 31, 2020, to assess the national accounts for the new base year 2016 with the National Institute of Statistics and Economic and Demographic Studies. (INSEED). These accounts were prepared in accordance with the System of National Accounts 2008 (2008 SNA). The proceedings took the form of a workshop with representatives of the World Bank, the United Nations Economic Commission for Africa (ECA), the African Development Bank (AfDB),the Statistical and Economic Observatory of Sub-Saharan Africa (AFRISTAT), the Commission of the West African Economic and Monetary Union (WAEMU) and the Central Bank of West African States (BCEAO). This report is largely based on the aide-memoire signed with the country and partners.